Pogansko bogovje slovanskega vzhoda in zahoda v luči slovenskih ljudskih pesmi Pagan Deities of the Slavic East and West in Slovene Folk Songs - Nartnik, Vlado (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Pagan gods of the Slavic East and West were outwardly extremely diverse. As a contrast to the double number of gods tied to different localities of the Slavic West, the six pagan gods of Slavic East mentioned in the treatise formed a rather harmonized system. Since Slovenes had been Christianized before any mention of either group of Slavic gods was recorded, the presence of their former pagan gods is reflected only in Slovene folk songs. The Slovene song heritage thus functions as a connecting link between the Slavic East and West.